An analysis of lifelong learning policies and practices of Regional Development Agencies - Yıldırım, Selcan Çınar. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2013., 2013)
This study aims to reveal how adult education activities are formulated in regional policies of the Regional Development Agencies (RDAs). To gather information, document analysis and semi-structured interviews are used. The semi-structured interview form is developed by the researcher and it is prepared for four different RDAs on April, 2013. The sample of the study is formed through nine persons who are experts of RDAs. Additionally, content analysis was used as a research method to make a document analysis of the RDAs’ lifelong learning policies. The study mainly focuses on nine documents. Primary documents are mainly used as data sources, and the selection of these documents is designed to fit the specific research questions underpinning this study. Agencies are new structures that bring the harmonization process with the EU to life and embody private sector dynamism in their structures when Turkey’s history of development is considered. Agencies have played important roles in relation to “responding to market demands” which has been very popular in liberal discourse within the last ten years, as practitioners of supranational and national policies in the regions. Agencies produce practical solutions to market requirements through funds. Agencies provide funds to projects that aim to give occupational training to a variety of groups especially for these purposes. The results of the study demonstrate that adult education policies are generally instrumentalized to produce the output that can create the labor force which has the competence and equipment suitable for the labor markets and structured for small-scale and short-term economic objectives. Lifelong learning is not discussed in the social context. This causes human to be defined as an input – human capital – to be transformed into labor force.
Keywords: Adult learning.; Adult learning -- Methodology.